Effects of Grafting Methods on the Physicochemical Properties of Gluten-Curcumin Conjugate and Its Application in Frozen Dough - Jianying LIU; Yalu ZHENG; Ruhuan YUAN; Feng XUE; Xiaohui XIONG; Chen LI (Shipin gongye ke-ji)
In this study, the conjugate of curcumin and gluten were prepared through alkaline, ultrasonic, and enzymatic methods. The effects of grafting methods on physicochemical properties of gluten, rheology properties of frozen dough and the quality of resulted bread were evaluated. The results showed that the conjugation induced by alkaline, ultrasound, and enzyme led to the decreasing of free amino group content in the range of 26.98%~28.74%, and free sulfhydryl group content in the range of 10.80%~14.52%, respectively. The conjugation also resulted in the disrupture of intramolecular hydrogen bonding, changes of the secondary, tertiary structure and surface hydrophobicity, as well as increasing of particle size and thermal stability. The frozen dough with curcumin-gluten conjugate exhibited higher complex modulus, creep recovery and hardness than those without the conjugate. Furthermore, the incorporation of curcumin-gluten conjugate into frozen dough also helped to improve the loaf volume and the hardness of resulted bread. These results indicated that the conjugation between curcumin and gluten could prevent the deterioration of frozen dough. In addition, as compared with conjugate prepared from alkaline and enzymatic methods, the conjugate prepared from ultrasonic method showed the better ability in improving the quality of frozen dough.